Normal Jews?. Issue 3 (29th September 2022) - Stavans, Ilan
Abstract : This essay reviews the following works: Migrations: Poem, 1976–2020. By Gloria Gervitz. Translated from the Spanish by Mark Schafer. New York: New York Review Books, 2021. Pp. 304. 20.00 paperback. ISBN: 9781681375700. Polacos in Argentina: Polish Jews, Interwar Migration, and the Emergence of Transatlantic Jewish Culture. By Mariusz Kałczewiak. Tuscaloosa: University of Alabama Press, 2020. Pp. viii + 320. 49.95 hardcover. ISBN: 9780817320393. The Other/Argentina: Jews, Gender, and Sexuality in the Making of a Modern Nation. By Amy K. Kaminsky. Albany: State University of New York Press, 2021. Pp. xviii + 262. 95.00 hardcover. ISBN: 9781438483290. Competing Germanies: Nazi, Antifascist, and Jewish Theater in German Argentina, 1933–1965. By Robert Kelz. Ithaca, NY: Cornell University Press, 2020. Pp. 372. 25.95 paperback. ISBN: 9781501739866. Nuestra América: My Family in the Vertigo of Translation. By Claudio Lomnitz. New York: Other Press, 2021. Pp. 464. 27.99 hardcover. ISBN: 9781635420708. Nuestra América: Utopía y persistencia de una familia judía. By Claudio Lomnitz. Mexico City: Fondo de Cultura Económica, 2018. Pp. 336. 14.00 paperback. ISBN: 9786071660084. Revolutionary Visions: Jewish Life and Politics in Latin American Film. By Stephanie M. Pridgeon. Toronto: University of Toronto Press, 2020. Pp. ix + 208. 50.00 hardcover. ISBN: 9781487508142. Armed Jews in the Americas. Edited by Raanan Rein and David M. K. Sheinin. Leiden: E. J. Brill, 2021. Pp. 264. 142.00 hardcover. ISBN: 9789004462533. Family Papers: A Sephardic Journey through the Twentieth Century. By Sarah Abrevaya Stein. New York: Farrar, Straus and Giroux, 2019. Pp. vi + 336. 28.00 hardcover. ISBN: 9780374185428. La vocación desmesurada: Una biografía de Alberto Gerchunoff. By Mónica Szurmuk. Buenos Aires: Sudamericana Editorial, 2018. Pp. 431. 23.54 paperback. ISBN: 9789500761482. Portrayals of Jews in Contemporary Argentine Cinema: Rethinking Argentinidad . By Mirna Vohnsen. Suffolk: Tamesis Books, 2019. Pp. 205. 99.00 hardcover. ISBN: 9781855663374.